Lifestyle Patterns as a Modifiable Risk Factor for Late-life Cognitive Decline: A Narrative Review Regarding Dementia Prevention - Wajman, José R.; Mansur, Leticia L.; Yassuda, Monica S. (Current Aging Science, 2018)
Background: Dementias due to neurodegenerative disorders and more specifically, Alzheimer’s disease (AD) are the most frequent of all diseases within the industrialized world. Besides this alarming fact, it is noted too that almost three-quarter of people with AD reside in low or middle- income nations. In recent years, cognitive and behavioral neuroscientists have focused on a possible correlation between environmental agents and genetic risk factors for these dementias. Methods: In this narrative review, a close review of Medical Literature Analysis and Retrieval System was conducted. The authors aimed at analyzing possible interactions between lifestyle patterns and major risk factors responsible for cognitive decline and dementia, considering that the prevention or treatment of midlife modifiable risks may possibly reduce population-wide late-life pathological neurodegeneration. Results: This review focuses on modifiable risk factors for late-life cognitive decline. A growing number of studies have indicated that the impact of genetics and epigenetic factors on dementia risk is dependent on different lifestyle factors, ranging from leisure activities and nutritional habits, through to social interaction and toxic exposure. Conclusion: Despite all evidence regarding modifiable risk factors possibly reducing the risk of developing dementia in later life, many unanswered questions remain regarding the direct influence of these variables in later life. People who regularly and actively participate in different lifelong activities (social, cultural and intellectual) do tend to perform better on formal cognitive tests, experience fewer cognitive complaints, and are less likely to develop neurodegenerative disorders.
Keywords: dementia